PERILAKU MASYARAKAT TERHADAP OPERASI BUKTI PELANGGARAN (TILANG) DALAM BERLALU LINTAS - Junef, Muhar (E-Journal Widya Yustisia, 2017)
One of the main problems in the pass-cross was Helms which resulted in inflicting casualties and losses of material. The behavior of the community is very decisive in the offences in traffic. The purpose of this research are to know: (1) the behavior of the community towards the operational proof of violations (speeding tickets) in the current traffic, (2) the behavior of the people who are supposed to be operating against the evidence of the offence (Ticketed) in traffic. The method used is descriptive library research with normative juridical approach. The results found that: (1) there has been no change to the operation of the community with evidence of behavior violations (speeding tickets) in traffic. This is a lot of road users who ignore traffic rules so as to trigger the occurrence of accidents, (2) the community should conduct operations against proof of offence (ticketed) in traffic can not only given meaning as the roas user, because user/individual can road users and also individuals representing corporations.